DDIS-02. NOVEL BISPECIFIC ACTIVATOR OF MACROPHAGES FOR THE TREATMENT OF GLIOBLASTOMA. (5th November 2018) - Salgado, Miguel; Schaller, Teilo; Gedeon, Patrick; Snyder, David; Archer, Gary; Sanchez-Perez, Luis; Sampson, John
Abstract: Patients undergoing current treatment for glioblastoma (GBM) still face a poor prognosis with a median survival of 16 months. Current therapy is incapacitating and limited by non-specific toxicity to the surrounding brain. We have developed an immunotherapeutic approach that selectively targets GBM by redirecting the patients' own macrophages present within the natural glioma milieu (representing up to 30% of the tumor volume) towards the tumor in an antigen-specific manner. This novel molecule, called bispecific activator of macrophages (BAM), bridges the macrophages with the tumor cells through the binding of CD64 and EGFRvIII, a tumor-specific antigen, respectively. We generated a stable fully human EGFRvIII-specific BAM Chinese hamster ovary cell line, and confirmed expression of BAM by western blot. Binding to CD64 and EGFRvIII was confirmed by flow cytometry on human CD64 + (hCD64) transgenic murine macrophages and EGFRvIII + gliomas. Simultaneous BAM engagement of hCD64 on macrophages, and EGFRvIII led to the induction of macrophage tumoricidal activity measured by reactive oxygen species release. Furthermore, in vivo BAMadministration into glioma bearing mice significantly reduced tumor growth. In conclusion, we have developed a novel immunotherapeutic approach capable of harnessing the body's own tumoricidal capacity by redirecting macrophages towards tumors via the administration of a bispecific activator of macrophages (BAM). While further studies are needed, this therapy offers promising results for the treatment of GBM.